VAT on intra-community trade and bilateral micro revenue clearing in the EU - Christian Breuer; Chang Woon Nam (Center for Economic Studies and ifo Institute (CESifo), 2009)
This study discusses European Commission's recent proposal to combat VAT fraud by taxing intra-Community supplies at a common rate of 15%, accompanied by the internal correction of input-tax gap between an importer and his own national tax authority, which is caused by the national VAT rate differing from 15%. It attempts to put this proposal into perspective by linking it to the overall aims of value added taxation in Europe and by comparing it to other alternative mechanisms examined in the literature. Especially issues of bilateral VAT revenue clearing between EU countries, which arise from the Commission's proposal, are highlighted.
Keywords: H87; H20; 330; value added tax; intra-EU trade; bilateral micro clearing; VAT fraud; European Union; Umsatzsteuer; EU-Steuerrecht; EU-Binnenhandel; Verrechnungsverkehr; Steuerkriminalität; EU-Staaten